Parental Rights, Best Interests and Significant Harms Medical decision-making on behalf of children post Great Ormond St vs Yates - Goold, Imogen; Herring, Jonathan; Auckland, Cressida (Hart Publishing, 2019)
This timely collection brings together philosophical, legal and sociological perspectives on the crucial question of who should make decisions about the fate of a child suffering from a serious illness. In particular, the collection looks at whether the current 'best interests' threshold is the appropriate boundary for legal intervention, or whether it would be more appropriate to adopt the 'risk of significant harm' approach proposed in Gard. It explores the roles of parents, doctors and the courts in making decisions on behalf of children, actively drawing on perspectives from the clinic as well as academia and practice. In doing so, it teases out the potential risks of inappropriate state intrusion in parental decision-making, and considers how we might address them.